2013
DOI: 10.1177/2042018813489719
|View full text |Cite
|
Sign up to set email alerts
|

Improving major amputation rates in the multicomplex diabetic foot patient: focus on the severity of peripheral arterial disease

Abstract: Objective: Peripheral arterial disease (PAD), as well as diabetic neuropathy, is a risk factor for the development of diabetic foot ulcers. The aim of this study was to evaluate differences and predictors of outcome parameters in patients with diabetic foot by stratifying these subjects according to the severity of PAD. Research design and methods: In a prospective study, patients with new diabetic foot ulcers have been treated and investigated by structured healthcare. Subjects were recruited between 1 Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 43 publications
(79 reference statements)
3
50
3
5
Order By: Relevance
“…In patients undergoing amputations, decreased ABI and transcutaneous oxygen pressure (both measurements of severity of PVD) have been shown to predict poor wound healing and increased level of primary amputation or reamputation. 17,18 Though our data only demonstrated a trend towards statistical significance, diabetes adversely affects wound healing and resistance to infection and also may contribute to readmissions in this patient population. Although it has been suggested that efforts to improve mobility may help to lower readmission rates, it is unclear the degree to which this strategy can overcome the inherent limitations of chronic comorbid conditions.…”
Section: Discussionmentioning
confidence: 52%
“…In patients undergoing amputations, decreased ABI and transcutaneous oxygen pressure (both measurements of severity of PVD) have been shown to predict poor wound healing and increased level of primary amputation or reamputation. 17,18 Though our data only demonstrated a trend towards statistical significance, diabetes adversely affects wound healing and resistance to infection and also may contribute to readmissions in this patient population. Although it has been suggested that efforts to improve mobility may help to lower readmission rates, it is unclear the degree to which this strategy can overcome the inherent limitations of chronic comorbid conditions.…”
Section: Discussionmentioning
confidence: 52%
“…From 9476 titles and abstracts, 156 articles were selected for full‐text review (Figure ). Of these, a total of 11 studies reporting on 5890 patients met the inclusion criteria and were included in the qualitative data synthesis (online Table 1, Appendix of the online data supplement). Most studies ( n = 7) were prospective; the remainder were retrospective ( n = 1), or did not specify ( n = 3) .…”
Section: Resultsmentioning
confidence: 99%
“…The mean or median age of cohorts studied ranged between 61 and 76 years; the proportion of men ranged between 59% and 74%. Seven studies reported on purely ulcerated patients, while two studies included patients with either active ulceration or gangrene at baseline . One study investigated the prognostic performance of PAD measures in patients with foot infection and/or ischemia (Fontaine III/IV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foot ulcers are one of the major health concerns and hospitalization among patients with diabetes, worldwide. In the USA, the yearly price of foot ulcers is estimated at US$11 billion (Brechow et al, 2013). In Brazil, the population 30 years old and over with type 2 diabetes is calculated at 6.5 million.…”
Section: Diabetic Foot Infectionsmentioning
confidence: 99%